IMPLEMENTASI MANAJEMEN MUTU DI SEKOLAH - Wijaya, M. Hengky (Managere: Indonesian Journal of Educational Management, 2019)
This paper explains about Implementation of quality in Philip B. Crosby's perspective in school educational institutions. School ducational institutions are a forum that has the function to produce quality individuals. To be able to produce a quality generation, of course an educational institution must be quality. The quality concept offered by Crosby to be implemented in educational institutions is to have fourteen stages, namely Management Commitment, Quality Improvement Team, Quality Measurement, The Cost of Quality, Quality Awareness, Corrective Actions, Zero Defects Planning, Supervisor Training, Zero Defects day, goal setting, Error-Cause Removal, Recognition, quality councils and do it over again. The fourteen stages will be implemented in school educational institutions as an effort to achieve quality school educational institutions.